Analisis Yuridis Konsep Hibah dalam Perspektif Hukum Islam dan Implementasinya dalam KHI (Kompilasi Hukum Islam) - Tiara Jelita Andalusianti Roozan; Diah Ajeng Pangestu; Adinda Berliana Rizkita Anjani; Vanesa Alexandra Caniago; Hasrinda Rizqi Pramassari; Rajwa Al Imtiyaz; Alan Saputra; Muhammad Reyvanza Anwar (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study examines the concept of hibah (gift) in Islamic law and its implementation in the Compilation of Islamic Law (KHI) in Indonesia. Through juridical-normative analysis, the research investigates how Islamic law principles regarding hibah have been transformed into national legislation through KHI and evaluates their implementation in religious court practices. The findings reveal that KHI has successfully harmonized Islamic jurisprudence with national legal requirements, particularly through articles 210-214, which regulate hibah procedures including limitations on gift amounts, beneficiary rights, and documentation requirements. However, challenges persist due to KHI's relatively weak position in the legal hierarchy as a Presidential Instruction rather than formal legislation, creating potential conflicts with other regulations. The study recommends strengthening KHI's legal status, updating its provisions to address contemporary issues, standardizing hibah procedures, and providing judges with appropriate discretionary space to ensure both legal certainty and substantive justice in hibah disputes.